Anxious Attachment as a Factor in Individual Survival in Toxic Relationships: A Phenomenological Study - Hafizha, Rizqa; Selian, Sri Nurhayati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Toxic relationships are a harmful interpersonal phenomenon commonly experienced by young adults, yet the decision to remain in such relationships is often difficult to understand. One psychological factor believed to play a role is anxious attachment, a pattern characterized by fear of abandonment and a high level of emotional dependence on a partner. This study aims to gain an in-depth understanding of the subjective experiences of individuals with anxious attachment tendencies who remain in toxic relationships. This study employed a qualitative approach with a phenomenological design. The participants consisted of three 19-year-old women who had experienced or were currently involved in unhealthy romantic relationships, selected through purposive sampling. Data were collected through in-depth semi-structured interviews and analyzed using phenomenological analysis. Four main themes were identified: unhealthy relationship dynamics characterized by emotional instability, overprotective behavior, and poor communication; emotional responses including sadness, overthinking, and fear of loss; factors contributing to staying centered on affection, hope for change, and temporary positive moments; and a process of self-awareness leading to personal growth. Anxious attachment was found to be a significant factor in maintaining individuals in toxic relationships; however, these experiences also open pathways for personal growth and a better understanding of healthy boundaries in romantic relationships.